Photoionization Processes of the Single-Ionized Boron. (16th February 2011) - Hsiao, Ju-Tang; Sun, Hsiao-Ling; Lin, Sheng-Fang; Huang, Keh-Ning
Abstract : The relativistic calculations of the cross-sectionσ, the angular-distribution parameterβ, and spin-polarization parameters{ ξ, η, ζ } of photoelectrons using the multiconfiguration relativistic random-phase approximation theory for the photoionization of theB + ion are presented. Precise energies and widths of all five Rydberg series of doublyexcited states( 2 p n s ) 1 P 1 o, ( 2 p n s ) 3 P 1 o, ( 2 p n d ) 1 P 1 o, ( 2 p n d ) 3 P 1 o, and( 2 p n d ) 3 D 1 o are determined. Our predictions are in very close agreement with experiments and are consistent with other calculations.